2017
DOI: 10.1042/bsr20171263
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive investigation of cytokine- and immune-related gene variants in HBV-associated hepatocellular carcinoma patients

Abstract: Host genotype may be closely related to the different outcomes of Hepatitis B virus (HBV) infection. To identify the association of variants and HBV infection, we comprehensively investigated the cytokine- and immune-related gene mutations in patients with HBV associated hepatocellular carcinoma (HBV-HCC). Fifty-three HBV-HCC patients, 53 self-healing cases (SH) with HBV infection history and 53 healthy controls (HCs) were recruited, the whole exon region of 404 genes were sequenced at >900× depth. Comprehensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Dianwu Liu et al suggested that thirty four variants of eight HLA genes, including HLA-B, HLA-C, HLA-DPA1, HLA-DQA1, HLA-DQB1, HLA-DQB2, HLA-DRB1 , and HLA-DRB5 , were strongly associated with HBV-related HCC 50. Weiping Zhou et al suggested that new associations at rs9272105 ( HLA-DQA1/DRB1 ) on 6p21.32 (odds ratio=1.30, P =1.13E-19) 51.…”
Section: Discussionmentioning
confidence: 99%
“…Dianwu Liu et al suggested that thirty four variants of eight HLA genes, including HLA-B, HLA-C, HLA-DPA1, HLA-DQA1, HLA-DQB1, HLA-DQB2, HLA-DRB1 , and HLA-DRB5 , were strongly associated with HBV-related HCC 50. Weiping Zhou et al suggested that new associations at rs9272105 ( HLA-DQA1/DRB1 ) on 6p21.32 (odds ratio=1.30, P =1.13E-19) 51.…”
Section: Discussionmentioning
confidence: 99%
“…We decided to use a target enrichment approach with in-solution hybridization capture of 100 annotated immune genes [ 24 ] to genotype a larger number of dromedaries tested for a recent infection of MERS-CoV. Targeted enrichment has successfully been applied in sequencing the IR genes of gopher tortoises [ 32 ], in assessing variants in immune genes associated with Hepatitis B virus infection [ 33 ] and in identifying somatic alterations in follicular dendritic cell sarcoma in known cancer-associated genes [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the course of chemotherapy for breast cancer patients, common chemotherapeutic drugs target non-cancer stem cells, but the cancer stem cells can survive and further cause recurrence or even metastasis due to their own characteristics. Therefore, breast cancer stem cells are considered to be the key population leading to drug resistance of breast cancer [ 14 , 15 ]. With the development of molecular markers of breast cancer stem cells, researchers have found that a small population of cells, selected by markers, can lead to the initiation of tumors, which further confirms the vital role of cancer stem cells in tumor initiation [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%